Impact of weedcontrol on amf propagules and mycorrhization of coffee trees - Melloni, Rogério; Silve, Emilienne Margueritte; Alvarenga, Maria Inês Nogueira; Melloni, Eliane Guimarães Pereira; de Alcântara, Elifas Nunes (Coffee Science - ISSN 1984-3909, 2017)
The maintenance of a diverse and active community of arbuscular mycorrhizal fungi (AMF) in the agricultural ecosystem is important for the sustainability of agro-systems such as coffee. This study aimed to evaluate the effect of different techniques of weed control applied in inter row the coffee plants, on the occurrence of arbuscular mycorrhizal fungi propagules, and consequently mycorrhization. This evaluation was carried out in a coffee plantation, at the Experimental Farm ofAgricultural Research Company of Minas Gerais (Epamig) in São Sebastião do Paraíso (MG). The tecnhiques of weed control were: 1) mower, 2) coffee tandem disk harrow, 3) rotary tiller, 4) pre and 5) post-emergence herbicide utilization, 6) manual hoe and 7) no weed control. The attributes evaluated were: intensity and mycorrhizal colonization, total and active length of mycelium in the soil, density and diversity of AMF spores. Among the weed control techniques applied to inter row the coffee plants, manual hoe, mover and coffee tandem disk harrow were the most favorthe maintenance of AMF propagules and mycorrhization of plants, contrary to the use of pre-emergence herbicide.